ANALISIS EKSPOR, IMPOR TERHADAP NERACA PERDAGANGAN DI EMPAT NEGARA EMERGING MARKET (RITI) - Darmawan, Alvin; Sari, Wahyu Indah (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
The goal of international trade between nations is to promote economic expansion. Based on the trade balance's findings, indicators of a nation's performance in international trade can be examined. The rate of economic growth, which can be evaluated from a number of angles, including the value of imports and exports, which affect a nation's trade balance, can be used to characterize a country's degree of success. The purpose of this study is to ascertain the short- and long-term effects of GDP, exports, imports, exchange rates, and GDP on the trade balance in four emerging market nations. The ARDL Panel Method was used to collect data from the World Bank between 2012 and 2022 for this study. There are therefore both long-term and short-term relationships. Over an extended period, the trade balance is largely influenced by exports, GDP, and exchange rates. Exports, meanwhile, have an immediate impact on the trade balance.